Study on the Challenges Factors in Implementing the Concept of Green Building in Wilayah Persekutuan Putrajaya - Bani, Fatin Nursyahira; Nagapan, Sasitharan (Recent Trends in Civil Engineering and Built Environment, 2024)
Concept of green building has been adapted to buildings in the Malaysian construction industries but there are many challenging issues in implementing green building projects in Malaysia. Therefore, the aim of this study is to identify the challenges factors in implementing the green building and to determine method to overcome in Malaysia. The research is using quantitative approach. The data has been collected using questionnaire survey. The questionnaires are distributed to 152 contractors in Wilayah Persekutuan Putrajaya. Respondents who successfully fill in the questionnaire was 63 contractors out of 152 of the targets. Response rate for the questionnaire was 41% only. The SPSS version 26 has been used to analyze the data acquired for this research. This study reveals and determine the challenges factors of practicing green building concept in construction industry. The collected data were analyzed using mean score and ranking methods. The three main challenge factors determined from the analysis were ‘High construction costs’ (mean score = 4.86), ‘Unwillingness to pay additional costs’ (mean score = 4.86) and ‘Limited availability of new technologies’ (mean score = 4.79). The top three methods to overcoming the challenges factors are ‘Green building contractors receive financial support’ (mean score = 4.83), ‘Government needs to publish information and benefits on green building to generate market demand’ (mean score = 4.83) and ‘Get training and activities for more knowledge and abilities’ (mean score = 4.76). Finally, this study able to create awareness amongst construction practitioners to enhance understanding about the challenges factors and the methods to overcomes the green building in construction industry.